Oxford new syllabus mathematics workbook 1 - Ban Har, Yeap (Karachi: Oxford University Press., 2024)
Oxford New Syllabus Mathematics Workbook 1 is a practice-focused supplement to the Oxford New Syllabus Mathematics 1 textbook. It provides students with a wide range of exercises and activities designed to reinforce their understanding of key mathematical concepts such as algebra, geometry, and number theory. The workbook emphasizes problem-solving skills and helps students apply theoretical knowledge to real-life situations. Through structured questions and progressive difficulty, students develop critical thinking and analytical abilities. This workbook is an essential tool for solidifying the foundational concepts introduced in the main textbook, ensuring a deeper grasp of mathematics.